FOSTERING DIGITAL FLUENCY: LIBRARIANS' TACTICS IN BRIDGING THE DIGITAL GAP AND MITIGATING DIGITAL MEMORY LOSS - Novianty Djafri; Hadenan Towpek; Mohd Syahrin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Fostering Digital Fluency: Librarians' Tactics in Bridging the Digital Gap and Mitigating Digital Memory Loss" delves into the multifaceted strategies librarians employ to address the challenges of digital literacy in today's rapidly evolving technological landscape. Through a comprehensive analysis of librarians' roles and initiatives, this study highlights the critical importance of fostering digital fluency among patrons. Librarians serve as crucial agents of change, leveraging their expertise and resources to provide educational programs, access to digital resources, and promotion of digital wellness. These tactics aim to empower individuals with essential digital skills, bridge the digital gap, and mitigate digital memory loss. The study underscores the significance of collaborative partnerships between libraries, community organizations, and stakeholders in amplifying the impact of digital literacy initiatives. Through collective efforts, these entities can address specific community needs and promote digital inclusion on a broader scale. Moreover, ongoing professional development and data-driven decision- making enhance librarians' effectiveness in fostering digital fluency and adapting to evolving technological trends. Ultimately, this research sheds light on the pivotal role of librarians in preparing individuals for success in an increasingly digital world. By equipping patrons with the necessary skills and knowledge to navigate the digital landscape confidently, librarians contribute to building a more equitable, informed, and digitally literate society.